Implementasi Akad Qardh pada Transaksi Utang Piutang di Bank Sedekah Nurul Falah Al-Mubarok Kabupaten Bekasi - Agustine, Hendra Karunia; Mashudi, Yudi; Fadiyah, Afifatul (Program Studi Hukum Ekonomi Syariah (Muamalah), 2025)
Sedekah Nurul Falah Al-Mubarok Bank appeared to provide account receivable transaction facilities based on qardh agreement sourced from the alms funds of its members. However, there are issues regarding the suitability of the agreement used with sharia principles. This study aims to determine and analyze the implementation of the qardh agreement in account receivable transaction at Nurul Falah Al-Mubarok charity bank in Bekasi regency based on the principles of Islamic law (fiqh muamalah). The method used was a qualitative approach with a case study. The main sources of data and information were obtained through in-depth interviews with administrators, members, foundation advisors, and religious leaders. The results of this study showed that this charity bank applies the concept of